2012
DOI: 10.1152/ajpregu.00023.2012
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring hypothermia is more advantageous than fever in severe forms of lipopolysaccharide- and Escherichia coli-induced systemic inflammation

Abstract: The natural switch from fever to hypothermia observed in the most severe cases of systemic inflammation is a phenomenon that continues to puzzle clinicians and scientists. The present study was the first to evaluate in direct experiments how the development of hypothermia vs. fever during severe forms of systemic inflammation impacts the pathophysiology of this malady and mortality rates in rats. Following administration of bacterial lipopolysaccharide (LPS; 5 or 18 mg/kg) or of a clinical Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 64 publications
5
101
2
7
Order By: Relevance
“…At least in some cases, the increased survival was coupled with a suppressed surge in ALT. 75 Whereas markers of hepatocyte damage were affected by hyperbilirubinemia in the present study, markers of renal disfunction (BUN and creatinine) were not (Fig. 3), thus suggesting the lack of tissue protection in the kidneys.…”
Section: Hyperbilirubinemia Attenuates Lps-induced Hepatic Damage In contrasting
confidence: 48%
See 1 more Smart Citation
“…At least in some cases, the increased survival was coupled with a suppressed surge in ALT. 75 Whereas markers of hepatocyte damage were affected by hyperbilirubinemia in the present study, markers of renal disfunction (BUN and creatinine) were not (Fig. 3), thus suggesting the lack of tissue protection in the kidneys.…”
Section: Hyperbilirubinemia Attenuates Lps-induced Hepatic Damage In contrasting
confidence: 48%
“…71 It involves cold-seeking behavior 42,72,73 and is thought to be aimed at decreasing the metabolic requirements of tissues. 3,71 In our studies, 74,75 when rats were either allowed to select their preferred low T a or maintained at a lower T a chosen by the investigators during endotoxin shock or Escherichia coli infection, their survival rates increased. At least in some cases, the increased survival was coupled with a suppressed surge in ALT.…”
Section: Hyperbilirubinemia Attenuates Lps-induced Hepatic Damage In mentioning
confidence: 73%
“…However, hypothermia may have positive effects on other aspects of pathophysiology independent of the thermal environment for the pathogen. For example, Liu et al (2012) found that rats that developed a ca. 2°C hypothermia after inoculation with severe doses of septic or aseptic endotoxins showed suppressed leakage of endotoxins into the bloodstream and reduced levels of visceral organ dysfunction, both of which probably contributed to lower mortality in hypothermic subjects.…”
Section: A Trade-off Between Foraging and Immune Function?mentioning
confidence: 99%
“…Hypothermia would be favoured when resources are scarce and the energetic costs of a fever response cannot be supported (Romanovsky and Székely, 1998). This can be the case during very severe infections or in energetically demanding environments (Liu et al, 2012), or in cases where insufficient body insulation and/or small body size precludes any sustained increase in body temperature (such as in neonates) because the resultant heat loss would be detrimental (Jones et al, 1983;Frafield and Kaplanski, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [20] showed that, despite the energy cost to the animal, in systemic inflammation induced by LPS or E. coli, hypothermia is more advantageous than fever because it reduces the organic dysfunction and the mortality rate.…”
Section: Discussionmentioning
confidence: 99%